Effects of slag content on the residual mechanical properties of ambient air-cured geopolymers exposed to elevated temperatures - Shaikh, Faiz (Taylor & Francis, 2018)
This paper presents the effects of various slag contents on the residual compressive strength and physical properties of ambient air-cured fly ash-slag blended geopolymers after exposure to various elevated temperatures up to 800°C. The results showed an increasing trend in the compressive strength of ambient air-cured geopolymers with increase in the slag contents after exposure to 400 and 600°C temperatures. This trend deviated, however, at 800°C. Nevertheless, all the geopolymers showed reductions in control compressive strength at ambient temperature after exposure to elevated temperatures. The reductions were much higher at 600 and 800°C compared to 400°C. All the geopolymers exhibited significant damage in terms of cracking after exposure to a temperature of 800°C compared to 400 and 600°C and significant damage occurred at slag contents of 15–30%. Scanning electron microscopic (SEM) images of the above geopolymers also showed higher porosity at 800°C compared to 400 and 600°C. Traces of calcite/calcium silicate hydrate (CSH) peaks are observed in the X-ray diffraction (XRD) analysis of fly ash-slag geopolymers, and the intensity of those peaks increased with increases in slag contents. After exposure to elevated temperatures, the calcite/CSH peaks disappeared and new phases of nepheline and gehlenite were formed at 800°C in all the fly ash-slag geopolymers.